ANALYSIS OF MILD STEEL CORROSION RATE BASED ON VARIATIONS OF ELECTRODES AND CORROSION MEDIA IN SMAW WELDING - Jefri Aldo (Department of Mechanical Engineering Education, 2026)
This study aims to determine the effect of electrode variations on mild steel plates using variations in corrosive environments. The method used in this study is experimental. Data collection techniques are carried out by documenting workpieces that have been welded using variations of electrodes dipped in variations of corrosion media for 15 days and observed using a digital microscope with a magnification of 50X. The results of this study show that workpieces that have been welded SMAW using variations of electrodes E6010, E6013, E7018 and using corrosive solutions of seawater and rainwater to be able to see the results of the development of the corrosion rate that occurs in the workpiece, which experiences a slow corrosion rate is found in the E6013 electrode using rainwater due to the strong current in the place when welding gets good results, and it is difficult for the corrosion rate to occur. While the type of E6010 electrode immersed in seawater solution shows a very rapid corrosion rate compared to other electrodes. The initial weight of the workpiece is 215.77 grams, and after 15 days of immersion, the weight of the workpiece decreases to 213.88 grams, resulting in a weight loss of 1.89 grams.